Implementasi Undang-Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat : (Studi Kasus Baitul Mal Kota Lhokseumawe) - Nazaruddin, Nazaruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2022)
This study aims to enhance the understanding of the community and the Baitul Mal administrators regarding zakat management in accordance with Law No. 23/2011 in Lhokseumawe City. The primary objective of this community service is to ensure effective zakat management practices that comply with Islamic law, thereby making a tangible contribution to poverty alleviation and the improvement of community welfare. The methodology of this study comprises several stages: 1) preparation, which includes initial coordination with Baitul Mal administrators and local government, and the development of research instruments; 2) implementation, which involves in-depth interviews and participatory observation of the zakat collection and distribution process; 3) data analysis using thematic analysis techniques; 4) comprehensive reporting delivered to relevant stakeholders; and 5) socialization through seminars, workshops, and training sessions. The results indicate a significant increase in the understanding of both the community and the Baitul Mal administrators about zakat management in accordance with Law No. 23/2011 following the socialization activities. The main challenges identified include a crisis of trust towards the government, lack of knowledge about zakat regulations, and difficulties in equitable distribution. The recommendations proposed include enhancing transparency and accountability in zakat management, improving training and education for Baitul Mal administrators and the community, and strengthening coordination between the government, Baitul Mal, and the community.